Compensatory responses to insulin resistance in obese African‐American and Latina girls. Issue 6 (2nd July 2013) - Hasson, R. E.; Adam, T. C.; Davis, J. N.; Watanabe, R. M.; Goran, M. I.
Summary Purpose Insulin responses to oral and intravenous glucose markedly differ by ethnicity. This study examined whether ethnic differences in pancreatic insulin secretion, hepatic insulin extraction and clearance explain these disparate findings in 35 obese African–American and 41 Latina girls (Tanner Stages: IV–V; ages: 14–18; body mass index percentile: 85.9–99.8%). Methods Pancreatic insulin secretion, hepatic insulin extraction and clearance were estimated by C‐peptide and insulin modeling during an oral glucose tolerance test. Insulin sensitivity (SI), acute insulin response to glucose (AIRG) and disposition index were derived from a frequently sampled intravenous glucose tolerance test. Results Compared to Latinas, obese African–American adolescents had lower pancreatic insulin secretion (21.3%; P < 0.01), glucose incremental area under the curve (IAUC) (41.7%, P = 0.02), C‐peptide IAUC (25.1%, P < 0.01) and SI (33.7%; P < 0.01). There were no ethnic differences in hepatic insulin extraction and clearance (P's > 0.05). Conclusions Compensatory mechanisms to insulin resistance do not appear to explain the ethnic differences in insulin responses to oral and intravenous glucose in obese African–American and Latina girls.